HOW TO DEVELOP CRITICAL THINKING SKILLS? - Kurbanbaeva Umida Erkaevna (Galaxy International Interdisciplinary Research Journal, 2022)
We know that critical thinking is understood as the expression of a person’s good and bad opinion of something and an event. Also the ability to think does not develop on its own, it must be developed and evaluated correctly. Moreover, evaluation can also increase a student’s ability to think critically. So, in the learning process, the question may arise as to how to evaluate and assess students ’critical thinking on various video materials, and this article provides information on how to evaluate students’ critical views on any event or video material.